Sandwich‐Like Reduced Graphene Oxide/Carbon Black/Amorphous Cobalt Borate Nanocomposites as Bifunctional Cathode Electrocatalyst in Rechargeable Zinc‐Air Batteries. Issue 27 (9th August 2018) - Sun, Jiqing; Yang, Dongjiang; Lowe, Sean; Zhang, Lijuan; Wang, Yazhou; Zhao, Shenlong; Liu, Porun; Wang, Yun; Tang, Zhiyong; Zhao, Huijun; Yao, Xiangdong
Abstract: The inhibitively high cost of the noble‐metal‐containing materials has become a major obstacle for the large‐scale application of rechargeable zinc‐air batteries (ZABs). To solve this problem in a practical way, a green and scalable method to prepare sandwich‐like reduced graphene oxide /carbon black/amorphous cobalt borate nanocomposites (rGO/CB/Co‐Bi ) is reported. These composites are shown to be a highly efficient and robust bifunctional electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). In this system, the spontaneous assembly of the GO sheet and CB nanoparticles is demonstrated by noncovalent interactions to build the sandwich‐like structure with hierarchical pore distribution. The impressive ORR and OER activities of the obtained nanocomposite are attributed to the high conductivity, large surface area, and the hierarchically porous channels. With room‐temperature synthesis and significant activities shown in the demonstrative battery test, the prepared nanocomposite can potentially serve as an alternative for noble‐metal‐based rechargeable ZAB cathode materials. Abstract : A sandwich‐like reduced graphene oxide/carbon black/amorphous cobalt borate nanocomposite built at room temperature shows impressive oxygen reduction and evolution activities. The activity benefits from the enhanced conductivity, enlarged surface area, and hierarchical pore distribution. The obtained nanocomposite displays remarkable activity and stability as the cathode in rechargeable zinc‐air batteries.